Systematic Review and Meta-Analysis Toward Synthesis of Thresholds of Ocean Acidification Impacts on Calcifying Pteropods and Interactions With Warming - Bednaršek, Nina; Feely, Richard Alan; Howes, Ella L.; Hunt, Brian P. V.; Kessouri, Faycal; León, Pablo; Lischka, Silke; Maas, Amy E.; McLaughlin, Karen; Nezlin, Nikolay P.; Sutula, Martha; Weisberg, Stephen B. (Frontiers in Marine Science, 2019)
Interpreting the vulnerability of pelagic calcifiers to ocean acidification (OA) is enhanced by understanding of their critical thresholds and how these thresholds are modified by other climate change stressors (e.g. warming). To address this need, we undertook a three-part data synthesis for pteropods, one of the calcifying zooplankton group. We conducted the first meta-analysis and threshold analysis of literature characterizing pteropod responses to OA and warming by synthetizing dataset comprising of 2097 datapoints. Meta-analysis revealed the extent to which responses among studies conducted on differing life stages and disparate geographies could be integrated into a common analysis. The results demonstrated reduced calcification, growth, development and survival to OA with increased magnitude of sensitivity in the early life stages, under prolonged duration, and with the concurrent exposure of OA and warming, but not species-specific sensitivity. Second, breakpoint analyses identified OA thresholds for several endpoints: dissolution (mild and severe), calcification, egg development, shell growth, and survival. Finally, consensus by a panel of pteropod experts was used to verify thresholds and assign confidence scores for five endpoints with sufficient signal:noise ratio to develop life-stage specific, duration-dependent thresholds. The range of aragonite saturation state from 1.5 to 0.9 provides a risk range from early warning to lethal impacts, thus providing rigorous basis for vulnerability assessments to guide climate change management responses, including evaluation of the efficacy of local pollution management. In addition, meta-analyses with OA and warming shows increased vulnerability in two pteropod processes, i.e. shell dissolution and survival, and thus pointing towards increased threshold sensitivity under combined stressor effect.